Sistema De Creencias Acerca de la Legitimación de La Violencia Conyugal en un Grupo De Mujeres Que Asisten al Centro De Atención Psicológica (2015)
For this present research is used methodology qualitative-descriptive, the overall objective is to analyze the beliefs that legitimize conjugal violence in a group of women who attend the Centro de Atencion Psicologica of the University Antonio Nariño, Bogotá, South headquarters. The specific objectives that guided the research process were: to identify beliefs within narratives that account for the legitimization of violence in women attending group counseling center.